Forensic accounting and fraud control in ASEAN - Muhammad Rizal Satria; Rima Sundari; Mubassiran Mubassiran (Indonesia Accounting Research Journal, 2026)
This study examines the extent to which forensic accounting practices influence fraud detection and fraud prevention across ASEAN countries. Prior studies largely rely on single-country settings and rarely compare multiple dimensions of forensic accounting within an integrated analytical framework, thereby limiting cross-country generalization. To address this gap, the present study simultaneously examines fraud investigation, litigation support, and dispute resolution within a regional ASEAN context. Unlike previous studies that analyse forensic accounting practices separately or within single institutional settings, this study develops an integrated cross-country model that evaluates the relative effects of multiple forensic accounting dimensions on fraud detection and prevention across ASEAN economies. Using a quantitative explanatory research design, data were collected through a structured questionnaire measured on a five-point Likert scale from 350 professionals working in auditing, forensic accounting, internal audit, and compliance functions across ASEAN countries, selected through purposive sampling. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM), including tests of validity, reliability, and bootstrapping to evaluate the measurement and structural models. In addition, a Multi-Group Analysis (MGA) was conducted to examine whether the structural relationships differ across ASEAN countries. The results indicate that fraud investigation and litigation support have strong positive effects on both fraud detection and fraud prevention, while dispute resolution shows a weaker yet statistically significant influence. These findings demonstrate the robustness of forensic accounting practices across different ASEAN institutional contexts. From a policy perspective, the results suggest that regulators and organizations in ASEAN should strengthen forensic investigation capacity and legal support mechanisms to enhance fraud control systems. However, the study is limited by its cross-sectional design, suggesting opportunities for future longitudinal research.